A Society of Solitaries: An Anglophone Literary Circle in Montreal - Frédette, Julie (Mémoires du livre / Studies in Book Culture, 2010)
Quebec has been home to a rich and vibrant English-language literary community since the nineteenth century. The rise of the Canadian small-press movement in the 1960s gave way to a revival of the English-language publishing industry in Montreal, which had considerably dwindled at the turn of the twentieth century. Poets benefited greatly from this phenomenon, and literary coteries of poets were formed as a result, in particular the Vehicule Poets, associated with the Véhicule Art Gallery and with Véhicule Press in the early 1970s, and a group of poets who were associated with New Delta and later with the Signal Editions poetry series. This paper focuses on the ways in which literary circles are formed and how they might be identified, and uses the Jubilate Circle, a group of poets revolving around Signal Editions and consisting of Michael Harris, David Solway, Carmine Starnino and Eric Ormsby, as a case study.